2019
DOI: 10.3233/jad-190364
|View full text |Cite
|
Sign up to set email alerts
|

Cognition Mediates the Relationship Between Sensory Function and Gait Speed in Older Adults: Evidence from the English Longitudinal Study of Ageing

Abstract: Background/Objective: Gait speed is an important indicator for assessing overall health status. Previous studies have reported the important role of sensory function in gait speed; however, the underlying mechanism is still unclear. This study aimed to examine whether cognition mediates the association of sensory function with gait speed among English older adults. Methods: Gait speed was assessed by "timed walking test". Hearing was measured by using a hearing screening device. Vision was self-reported. Cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…We found strong evidence of an independent association between sensory impairment parameters, particularly, HI [28][29][30]33 and VI, 28,31,34 and slow gait speed. For instance, Chen and coworkers 33 in an 11-year longitudinal study of US adults aged ≥70 years found that subjects with HI had slower slow gait speed than those with no HI.…”
Section: Sensory Impairments and Gait Speedmentioning
confidence: 50%
See 2 more Smart Citations
“…We found strong evidence of an independent association between sensory impairment parameters, particularly, HI [28][29][30]33 and VI, 28,31,34 and slow gait speed. For instance, Chen and coworkers 33 in an 11-year longitudinal study of US adults aged ≥70 years found that subjects with HI had slower slow gait speed than those with no HI.…”
Section: Sensory Impairments and Gait Speedmentioning
confidence: 50%
“…Four studies drew from Asian populations, seven from Caucasian populations and two from a combination of multiple ethnicities from six low‐ and middle‐income countries (LMIC). Two studies 30 , 38 had a moderate (NOS 5–7) and the remaining 22 , 23 , 28 , 29 , 31 , 32 , 33 , 34 , 39 , 40 , 41 ( n = 11) had a low (NOS ≥ 8) risk of bias ( Table 2 for longitudinal studies; Table 3 for cross‐sectional studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Furthermore, the association between DSL and walking speed was reported in an English cohort of older adults. 18 However, most prior studies have been cross-sectional. This longitudinal study assesses the association between DSL and walking speed using a population-based sample of older adults in the United States, the Health and Retirement Study (HRS).…”
mentioning
confidence: 99%
“…Nesse sentido, é importante ressaltar a importância do sistema cognitivo 76 , que, entre as suas funções, permite que um indivíduo seja capaz de organizar os padrões de movimento direcionados a um certo objetivo, papel conhecido como planejamento motor 77 . Além disso, também permite que a atenção seja dividida entre diferentes demandas 66,67,76 , como ocorre, por exemplo, quando se conversa ao caminhar.…”
Section: Mobilidade Funcional Na Pessoa Idosaunclassified